in maths its a sum so 4 x 2 = 8 in measurements it will be length x width or height x base
You need to rephrase your question. Do you mean "what is the value of x if...", or do you mean "what is this expression"? If you mean to find the value of x, the answer depends on your phrasing of the question. It reads like this: √x + 2 = √x + 2 which is meaningless. It's the same as saying "x = x". You could however also mean: √(x + 2) = √x + 2 Which is a somewhat more interesting problem. You can solve for x by squaring both sides and reducing to simplest terms: √(x + 2) = √x + 2 x + 2 = x + 4√x + 4 4√x + 2 = 0 √x = -1 / 2 x = ± i / 4
If you mean 2 x 2 (4) x 2 (8) x 2 (16), then it is 18446744073709551616.If you mean 2 x 64 it is 128.
If you mean what is b4 x b2, the answer is b6...
x^2/x +2=4/x +2 (x^2/x)-(4/x)=0 (x^2-4)/x=0 x^2-4=0 (x+2)(x-2)=0 x=±2
x/4 - 4 = -2 Therefore, x/4 = -2 + 4 = 2 Therefore, x = 2 x 4 x = 8
-2
6
mean = (4 + 81)/2 = 85/2 = 42.5
If you mean: 4(2x-2) = 4-4(x-3) then the value of x works out as 2
If you mean: 4(x-2) = 0 then 4x-8 = 0 and x = 2
If you mean: (x-2)(x+4) = 0 then it is a quadratic equation whose solutions are x = 2 or x = -4
If you mean: (x - 2)2 Then it can be expanded to: x2 - 4x + 4 If you mean: (x - 2)2 Then it is the same as: 2(x - 2) and can be expanded to: 2x - 4 If you mean: x(-2)2 Then the terms are all multiplied together (a lack of operator between a term and adjacent parentheses indicates multiplication. i.e. 2(3) is the same as 2 × 3): -4x And finally if you mean: x - (2)2 Then the answer is: x - 4
If you mean: (x-4)(x+12) then it is x^2 +8x -48
You need to rephrase your question. Do you mean "what is the value of x if...", or do you mean "what is this expression"? If you mean to find the value of x, the answer depends on your phrasing of the question. It reads like this: √x + 2 = √x + 2 which is meaningless. It's the same as saying "x = x". You could however also mean: √(x + 2) = √x + 2 Which is a somewhat more interesting problem. You can solve for x by squaring both sides and reducing to simplest terms: √(x + 2) = √x + 2 x + 2 = x + 4√x + 4 4√x + 2 = 0 √x = -1 / 2 x = ± i / 4
If you mean: x^2 +5x +4 then it is (x+4)(x+1) when factored
If you mean: 2*(x-4) = 73 then the value of x works out as 40.5
x squared. for example, if you will substitute "4" from "x" then,x=4;x²=4²=16. the small 2 indicates that you will multiply the number by itself.